Numerical Assessment of Orthographic Neighbourhood Size Fluctuation in Writing Using Fractal Dimension Analysis. Issue 3 (3rd July 2021) - Taibu, Rex; Cheung, Eric; Ye, Weier; Dehipawala, Sunil; Shekoyan, Vazgen; Tremberger, George; Cheung, Tak
ABSTRACT: The orthographic size of a targeted word, the number of new words that can be generated from a targeted word by exchanging a single letter, offers a research window where words can be transformed into numerical values. The CLEARPOND technology from Northwestern University was used for the transformation. A writing can then be modelled as a time series where the fluctuation can be further described using fractal dimension analysis. This project used the Higuchi fractal method for the computation of the fractal dimensions of time series. The proof of concept was conducted using writing examples which include Astronomy writing and English writing, the responses of Trump and Clinton in a Presidential election debate, and song lyrics. The results suggested that a high fractal dimension has an association with a high-demand cognitive task. The use of fractal dimension analysis as a writing assessment tool is discussed with relationship to the current lexical diversity computation technology.